107 Differences in determinants amongst individuals reporting residential fires in Sweden – results from a cross-sectional study. (1st September 2016) - Nilson, Finn; Bonander, Carl; Jonsson, Anders
Abstract : Background: Whilst determinants for fire mortality and morbidity are well documented, the determinants of residential fires, regardless of outcome, are less known. This study aimed to investigate socio-demographic differences between households having experienced a fire and those who had not. Method: Using a cross-sectional study design, a questionnaire was sent to a stratified sample ( n = 20, 000) of the Swedish population regarding if the household had experienced a fire during the past 5 years. Pearson's χ 2 -test was used to test for bivariate associations between residential fires and socio-demographic covariates, and log-binomial regression models were applied to obtain covariate-adjusted risk ratios. Results: Significant factors associated with an increased risk of residential fires were a high education level, being born outside of the Nordic countries and having children 6–12 years living at home. A significant decreased risk was observed amongst elderly and those living in rented, multi-family houses. Discussion: There seems to be a lack of agreement between determinants for fires and for fire mortality. This would indicate that the risk of fire mortality per residential fire is greatly increased for certain groups and that the increased risk of fire mortality is not due to a more common occurrence of fires. Published in Fire Technology, May 2015, Volume 51, Issue 3, pp 615–626